"Passata è la tempesta …”. A land use planning vision for the Italian Mezzogiorno in the post pandemic - La Greca, Paolo; Martinico, Francesco; Nigrelli, Fausto Carmelo (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The Covid-19 pandemic event can activate a comprehensive reflection on the change of development models, overcoming the current unsustainable ones. Present events in Italy are mainly affecting Northern Regions but also the Southern ones will suffer from economic consequences, related to the pandemic. This is particularly relevant for the marginal areas of the Italian Mezzogiorno. The article highlights issues that are deemed relevant for including inner areas of Italian Southern regions into the process of economic recovery after the pandemic, in order to avoid the deepening of the long lasting North South imbalance, in the light of the growing depopulation of this part of the Country. The focus is on the role of Health Services, Education, Built up Environment and Transports, systems considered as key elements for promoting a well-balanced use of existing territorial assets. The real challenge is to reverse this terrible threat into an opportunity, introducing effective changes into the way we waste our limited planetary resources, especially the territorial ones. In this direction, Southern regions can play a fundamental role for increasing the resilience of the entire nation.